The study of humidity sensors having sandwich structure based on chalcogenide glasses - Alekberov, R.I. (JOURNAL OF ADVANCES IN PHYSICS, 2016)
This article is devoted to the study of the influence of moisture in sandwich structure Al-As33.3Se33.3S33.4-Te, Al- As33.3Se33.3S33.4:Smx-Te (x=1 at%).It is clear from the analysis of schedules, after thermal annealing time characteristics is improved for the sample doped by Sm.After thermal annealing decreases 2-4 times inertia inAs33.3Se33.3S33.4:Smx (x=1 at%).This increases the possibility applying of humidity sensors.